Analisis Konten Instagram Polsek Tanjung Priok Sebagai Wadah Informasi Publik - Siti Dwijayaty Nur Hasan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research analysis the content of the messages found in the feed (photos, videos, and reels) uploaded on the Instagram account @polsek_tanjung_priok in communicating public information, including the types of activities displayed on that account. Social media is utilized by various government agencies, including the National Police, with the aim of disseminating information and enhancing reputation, as well as serving as a means of online documentation. One of the popular social media platforms is Instagram; Instagram is not only a platform for sharing photos and videos but also a means to access news, information, and educational content. This research was conducted with the aim of analyzing the content of the messages found in the posts uploaded on the Instagram account @polsek_tanjung_priok in conveying public information, including the types of activities displayed. This research uses qualitative research methodology with content analysis research method. The results show that the content of messages found in the feed (photos, videos, and Reels) uploaded on the Instagram account @polsek_tanjung_priok in conveying public information contains various messages in the form of information aimed at the community, especially in the Tanjung Priok District of North Jakarta, utilizing social media Instagram for various purposes and delivered through various means, including appeals that are persuasive or warnings, news that conveys current events, and Instagram hashtags intended to categorize content on social media.